Pelatihan Sepak Bola Berbasis Permainan untuk Meningkatkan Kerjasama Tim di Kalangan Siswa SD Negeri 156 Buntu - Arga, Arga; Arba', Muhammad Arkanul; Rerung, Charmila Tandi; Hasanuddin, M. Imran; Hasyim, Muhammad Qasash; Fahrizal, Fahrizal (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
This community service activity in the form of game-based football training aims to improve teamwork skills in elementary school students through a fun and inclusive approach. The activity was carried out at SD Negeri 156 Buntu, Gandangbatu Sillanan District, Tana Toraja Regency, South Sulawesi with the involvement of 30 students as participants. The methods used in this training are demonstrations, hands-on practice, and evaluation through modified soccer games that emphasize the cooperation aspect. The training was carried out for 8 weeks with the intensity of meetings 2 times a week. The results showed a significant improvement in teamwork skills, communication between players, and basic football skills in participants measured through structured observation and feedback questionnaires. The biggest improvement was seen in the aspect of verbal communication when playing and the willingness to share the ball with teammates. This activity has a positive impact on the development of social and physical skills of students in rural areas who have limited access to quality sports training.